Architectures - Copans, Richard; Neumann, Stan (France : ARTE France, 2003)
A series devoted to the most ambitious architectural creations of the 19th and 20th century, consisting of remarkable archive material, scale-models, and interviews with some of the greatest architects of our time
Architectures 1 (163 min.) - Architectures 2 (136 min.) - Architectures 3 (160 min.) - Architectures 4 (160 min.)
DVD Format
In German, English, and French versions
Keywords: Architecture -- 20th century; Architecture -- 19th century; Documentary films